The Role of the Indonesian Military in Early Independence: Nationalist and Socialist-Communist Views - Nugroho, Arifin Suryo (JSSH (Jurnal Sains Sosial dan Humaniora), 2025)
In the early years of Indonesia’s independence, the role and position of the military became a subject of debate involving various ideological perspectives, particularly between nationalist and socialist-communist factions. The nationalist group tended to view the military as a state apparatus responsible for maintaining national stability and sovereignty, while the socialist-communist faction saw it as a revolutionary force that should actively participate in class struggle and social transformation. These differing perspectives influenced military policies and the relationship between the military and civilian government, creating tensions that led to various political dynamics. This article analyzes how these two perspectives shaped the doctrine and policies of the Indonesian military and their impact on civil-military relations throughout the nation’s history. Using a historical approach and document analysis, this study aims to examine how these two perspectives influenced the concept and discourse on the role of the Indonesian military in politics during the early independence period.